Understanding Adolescence’s Experiences in Using “Study with Me” Content Video - Yunianto, Paramita; Putridinanti , Maudy (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
The rise of technology is constantly evolving rapidly. Changes in behaviour have emerged in society as a result of technology growth. For instance, it can be easily influenced by content consumed in daily life, such as concepts changes in independent learning. When entering the quarantine for a long period of time, the changes in self-study behaviour begin to appear. Furthermore, when viewers require high concentration at home as well as they need to search for a good ambience at the same time so they will seek encouragement to learn in quarantine. One of the content is study with me on YouTube platform, which entails recording yourself doing independent learning activities over an extended period of time. This type of content has become extremely popular among millennials and gen Z generations. The usage of background or ambience in this content also plays an important function in capturing viewers' interest in understanding the subject. as a "study friend" related to emotional attraction This phenomena encouraged us to investigate how viewers comprehend and interact with and comprehend “Study With Me”. This paper uses phenomenological research to examine how research participants understand information such as behaviour, perception, and motivation as an effective "study partner" By analysing the motivations and viewing habits of subject who watched "study with me.” As a result, viewers watch “study with me” videos to satisfy their needs on studying independently to gain motivation and emotional support. Our findings suggest opportunities of how people’s understanding of the which improves people's study experience not just for a few highly motivated people but also the one who finds its struggle to create personalized ambience.